Análise de recursos audiovisuais utilizados por docentes do ensino superior nas disciplinas de Libras - Fornari, Rodrigo Vecchio (2021)
The Brazilian Sign Language is a visual-gestural language, and its learning takes place mainly through the visual channel. Therefore, the audiovisual resources present in didactic materials for the teaching of Libras in undergraduate courses must prioritize image and content quality. A few years ago, recording, editing, and sharing a video was only possible for communication professionals or those directly linked to the audiovisual market. Today, thanks to advances in technology and the popularization of smartphones and personal computers, these tasks are performed by “ordinary people”, requiring only a little interest and curiosity to achieve these feats. However, this intuitive use of equipment and tools for video production can cause technical problems that affect the final quality of these materials. In view of this, this research aims to analyze audiovisual resources for the teaching and learning Libras as a second language (L2) for hearing students. For this purpose, it was decided to carry out a exploratory-descriptive research, with analysis of materials produced and/or used by teachers of Libras, of intermediate or advanced level, of the presential courses of licentiate and baccalaureate that aim at the formation of teachers, translators, and sign language interpreters, from Federal Educational Institutions. The professors at these institutions were contacted and, through an online form, an attempt was made to outline the profile of the participants. Interviews were carried out with some participants, aiming at a better understanding of the process of elaboration or choice of audiovisual materials. Subsequently, they were asked to send or indicate the audiovisual material used for analysis purposes. The material collected was presented in the analysis and the discussions and reflections are based on the literature in the areas of visuality and technology. As a result, this research demonstrates the need for technical support and complementary training aimed at these teachers to produce materials with audiovisual resources for their classes, resources that are extremely relevant for hearing learners. The technical analysis of the materials sent allowed the formulation of guidelines and recommendations for capturing, editing, and sharing videos to produce new, more efficient, and assertive materials for the Libras disciplines.